The impact of a private sector living wage intervention on consumption and cardiovascular disease risk factors in a middle income country - David H. Rehkopf; Katharine Burmaster; John C. Landefeld; Sarah Adler-Milstein; Emily P. Flynn; Maria Cecilia Acevedo; Jessica C. Jones-Smith; Nancy Adler; Lia C. H. Fernald (BMC, 2018)
Abstract Background A positive association of socioeconomic position and health is well established in high-income countries. In poorer nations, however, higher income individuals often have more cardiovascular risk factors (including obesity) than do those with less income. Our study goal was to estimate the effects of receiving a living wage (340% higher income) on short-term changes in consumption and cardiovascular risk factors among low-wage workers in a middle-income country. Methods This cross-sectional study matched workers at an apparel factory (n=105) in the Dominican Republic with those at a similar factory (n=99) nearby, 15 months after the intervention factory introduced a substantially higher living wage. Statistical matching on non-time varying individual characteristics (childhood health, childhood living conditions, work experience, demographic factors) strengthened causal inference. Primary outcomes were blood pressure (systolic and diastolic), pulse rate, body mass index and waist circumference. Secondary outcomes were dietary consumption and spending on services, consumables and durable goods. Results Receiving the living wage was associated with increased consumption of protein, dairy, soda and juice and sugars, but not with cardiovascular risk factors. Intervention factory workers spent more on grocery items and household durable goods. Conclusions While having a higher income in a middle-income country might be expected to increase obesity and its associated health risks, the current study found no short-term negative associations. There may be possible longer-term negative health consequences of increases in consumption of soda, juice and sugars, however. It is important to consider complementary interventions to support healthy dietary intake in areas with increasing wages.